Development of an Indirect ELISA for the Detection of SARS-CoV-2 Antibodies in Cats - Bold, Dashzeveg; Roman-Sosa, Gleyder; Gaudreault, Natasha N.; Zayat, Batsukh; Pogranichniy, Roman M.; Richt, Juergen A. (Frontiers in Veterinary Science, 2022)
Companion animals are susceptible to a variety of coronaviruses and recent studies show that felines are highly susceptible to SARS-CoV-2 infection. RT-PCR diagnostics are currently the method of choice to detect the presence of SARS-CoV-2-specific viral nucleic acids in animal samples during an active infection; however, serological assays are critical to determine if animals were exposed to the virus and to determine the seroprevalence of SARS-CoV-2-specific antibodies in a defined population. In this study, we utilized recombinant nucleocapsid (N) protein and the receptor binding domain (RBD) of the SARS-CoV-2 spike protein, expressed in E.coli (N) and mammalian cells (N, RBD) to develop indirect ELISA (iELISA) tests using well characterized SARS-CoV-2 positive and negative cat serum panels from previous experimental cat challenge studies. The optimal conditions for the iELISA tests were established based on checkerboard dilutions of antigens and antibodies. The diagnostic sensitivity for the detection of feline antibodies specific for the N or RBD proteins of the iELISA tests were between 93.3%-97.8%, and the diagnostic specificity 95.5%. The iELISAs developed here can be used for high throughput screening of cat sera for the presence of SARS-CoV-2-specific antibodies in a BSL-2 biocontainment environment, unlike virus neutralization tests with live virus which have to be performed in BSL-3 laboratories.